TGF-β superfamily members from the helminth Fasciola hepatica show intrinsic effects on viability and development - Japa, Ornampai; Hodgkinson, Jane E.; Emes, Richard D.; Flynn, Robin J. (EDP Sciences, 2015)
The helminth Fasciola hepatica causes fasciolosis throughout the world, a major disease of livestock and an emerging zoonotic disease in humans. Sustainable control mechanisms such as vaccination are urgently required. To discover potential vaccine targets we undertook a genome screen to identify members of the transforming growth factor (TGF) family of proteins. Herein we describe the discovery of three ligands belonging to this superfamily and the cloning and characterisation of an activin/TGF like molecule we term FhTLM. FhTLM has a limited expression pattern both temporally across the parasite stages but also spatially within the worm. Furthermore, a recombinant form of this protein is able to enhance the rate (or magnitude) of multiple developmental processes of the parasite indicating a conserved role for this protein superfamily in the developmental biology of a major trematode parasite. Our study demonstrates for the first time the existence of this protein superfamily within F. hepatica and assigns a function to one of the three identified ligands. Moreover further exploration of this superfamily may yield future targets for diagnostic or vaccination purposes due to its stage restricted expression and functional role.